A novel semi-dominant mutation in brassinosteroid signaling kinase1 increases stomatal density - Ando, Eigo; Taki, Kyomi; Suzuki, Takamasa; Kinoshita, Toshinori (Frontiers in Plant Science, 2024)
Stomata play a pivotal role in balancing CO2 uptake for photosynthesis and water loss via transpiration. Thus, appropriate regulation of stomatal movement and its formation are crucial for plant growth and survival. Red and blue light induce phosphorylation of the C-terminal residue of the plasma membrane (PM) H + -ATPase, threonine, in guard cells, generating the driving force for stomatal opening. While significant progress has been made in understanding the regulatory mechanism of PM H + -ATPase in guard cells, the regulatory components for the phosphorylation of PM H + -ATPase have not been fully elucidated. Recently, we established a new immunohistochemical technique for detecting guard-cell PM H + -ATPase phosphorylation using leaves, which was expected to facilitate investigations with a single leaf. In this study, we applied the technique to genetic screening experiment to explore novel regulators for the phosphorylation of PM H + -ATPase in guard cells, as well as stomatal development. We successfully performed phenotyping using a single leaf. During the experiment, we identified a mutant exhibiting high stomatal density, jozetsu (jzt), named after a Japanese word meaning 'talkative'. We found that a novel semi-dominant mutation in BRASSINOSTEROID SIGNALING KINASE1 (BSK1) is responsible for the phenotype in jzt mutant. The present results demonstrate that the new immunohistochemical technique has a wide range of applications, and the novel mutation would provide genetic tool to expand our understanding of plant development mediated by brassinosteroid signaling.